PENGARUH PEMERIKSAAN PAJAK PENAGIHAN PAJAK DAN KEPATUHAN WAJIB PAJAK TERHADAP PENERIMAAN PAJAK DI KOTA BATAM - manurung, selly; Banjarnahor, Haposan (LPPM Universitas Putera Batam, 2020)
Tax is the biggest source of income in Indonesia in financing development. Efforst to maximizestate revenue cannot be depend rely on by the role of the Director General of Taxes or TaxOfficials, but also the active role of taxpayers. The purpose of the this study is to find empiricalevidence about the influence of tax audits, tax collections and taxpayer compliance on taxrevenue. The sample used in this study was 100 respondents. The data collection method usesbasic data of obtained from the Questionnaire distribution to research respondents. The datacollected in this study is multiple linear regression analysis with the using SPSS. The results ofthe study showed that tax audits, tax colletion and taxpayer compliance in silmutan and partialhave a significantly effect on tax revenue. Tax audits has not an effect on tax revenue. Taxcollection has an effect on tax revenue. Taxpayer compliance has an effect on tax revenue.